The Effect of Dietary Protein and Energy Levels During the Growing Period of Egg-type Pullets on Early Egg Production and Egg Weight and Dimensions in Arid Hot Climate - Babiker , M.S.; Abbas, M.A.; Kijora, C.; Danier, J. (International Journal of Poultry Science, 2010)
A (3 x 3) factorial arrangement was used in a completely randomized design to study the effect of early nutrition of pullet on subsequent egg production and quality. Three levels of protein and three levels of energy during stages of pullet growth (starter 0-6 wk, grower 7-12 wk and developer 13-18 wk of age) and their effect on laying performance (22-36 wk of age) were evaluated. In all phases of growing period, control levels of protein (P1) and energy (E1) were set according to NRC (1994) and the other levels were higher, for protein in 2% steps (P2 and P3) and for energy by 100 kcal of ME/kg steps (E2 and E3). Each treatment was replicated three times with ten birds each. Treatments in the factorial arrangement were kept the same for bird groups in every phase but at 19 week of age all groups were shifted to the identical layer diet up to the end of the trial. The layer performance of the different treatment groups was evaluated. In phase one of egg production cycle (22-36 week of age), hen-day egg production was influenced (p